CONTENT AND METHODS OF TESTING WRESTLERS - Баялиев, Рахым; Қонаев, Т. (SWorldJournal, 2020)
Wrestling is one of the oldest and most beloved sports, occupies an honorable place in the system of physical education, being a means of all-round physical development of people, strengthening their health, preparing for highly productive work. Wrestling